2018
DOI: 10.21037/jtd.2018.01.77
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after red blood cell transfusions from previously pregnant donors: complexities in the interpretation of large data

Abstract: Red blood cell (RBC) transfusion is a common and potentially life-saving intervention. The requirement for RBC transfusions inherently reflects a degree of illness in the recipient, and healthy individuals do not generally require blood transfusions. In the recent past, restrictive blood transfusion policies have improved patient outcomes with the added benefit of driving down medical costs (1). Other policies and advances in cell preservation technology such as ABO and Rh matching, leukoreduction and limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The availability of large data warehouses linking donors and their characteristics to recipients and their outcomes provides enormous scientific potential. However, questions asked of this data must be carefully analysed given the risk for subtle confounding [19,23]. The current evidence for increased mortality associated with sex-mismatching between red cell donors and recipients is conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of large data warehouses linking donors and their characteristics to recipients and their outcomes provides enormous scientific potential. However, questions asked of this data must be carefully analysed given the risk for subtle confounding [19,23]. The current evidence for increased mortality associated with sex-mismatching between red cell donors and recipients is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of case-mix. As pointed out by Kuldanek and Silliman, a young-male population may be enriched for trauma victims, who would be at increased risk for both massive transfusion and increased mortality by virtue of their underlying illness [19].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Previous studies suggested that the storage time of red blood cells (RBCs) may lead to immunosuppression. 4 , 5 RBCs undergo morphologic and functional changes during the duration for storage 6 (what is called “storage lesions”), including imbalance of the cell membrane expression of CD47 and phosphatidylserine, which can contribute to activate the immune system. 7 Moreover, during storage, cytokines and other immunomodulatory substances accumulate in the supernatant and trigger the activation of immune cells.…”
Section: Introductionmentioning
confidence: 99%